The stuffed crocodile of "Castel Nuovo" in Naples (Italy): new insights from ancient DNA and radiocarbon. Issue 1 (1st January 2020) - Fioravanti, T.; Casafredda, E.; Splendiani, A.; Caputo Barucchi, V.
Abstract: In the present study, a stuffed crocodile displayed for centuries at the "Castel Nuovo" (New Castle) in Naples was radiocarbon dated and examined using ancient DNA analysis. The specimen was classified as Crocodylus niloticus based on its large body size and the mitochondrial DNA haplotype obtained, already described for a living population in Lake Nasser (Egypt). Radiocarbon analysis indicated an age of 585 ± 40 14 C year BP, which coincides with the end of the Middle Ages. These results are commented in the light of Medieval religious symbolism and ancient legends which link the crocodile to the history of Naples during the mid-fifteenth century. The data obtained seem to confirm the explanation found in an old guidebook to Naples, according to which the stuffed crocodile was offered by a soldier returning from Egypt as an ex-voto to the image of the "Madonna del Parto" in the chapel of the castle. In addition, the radiocarbon dating shows that the individual analysed could be the oldest taxidermied vertebrate in Europe.